1993
DOI: 10.1128/jb.175.24.7819-7827.1993
|View full text |Cite
|
Sign up to set email alerts
|

Role of disulfide bonds in maintaining the structural integrity of the sheath of Leptothrix discophora SP-6

Abstract: Isolated sheaths of Leptothrix discophora SP-6 (ATCC 51168) were tested for susceptibility to degradation by a variety of chemical denaturants and lytic enzymes and found to be resistant to many reagents and enzyme treatments. However, disulfide bond-reducing agents such as dithiothreitol (DTT), P-mercaptoethanol, sodium cyanide, and sodium sulfite degraded the sheath, especially at elevated pH (pH 9) and temperature (50°C). DTT and 1-mercaptoethanol caused more rapid degradation of the sheath than cyanide or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…They appeared to be integral structural elements of the inner condensed sheath layer. This interpretation was confirmed in later sheath dissociation studies (20). No subunit structure was FIG.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…They appeared to be integral structural elements of the inner condensed sheath layer. This interpretation was confirmed in later sheath dissociation studies (20). No subunit structure was FIG.…”
Section: Resultssupporting
confidence: 70%
“…Here we confirm that the ultrastructure and chemical com-position of intact cellular filaments and cell-free sheaths of L. discophora sheath proteins contain a high relative abundance of cysteine residues which provide sulfhydryls for the disulfide bonding responsible for maintaining the structural integrity of the sheath (20). (A preliminary report of this work was presented previously [18].)…”
supporting
confidence: 63%
“…Leptothrix species deposit copious amounts of iron hydroxide-encrusted sheaths in the environment where they grow [4]. Chemically active saccharic and proteinaceous groups in the secretions of bacteria are thought to play a key role in binding aqueous inorganic ions [4,9,11,12,[34][35][36][37]. Although Hashimoto et al [18] found a variety of chemical bonds such as Fe-O, Fe-O-Si, Fe-O-P and so on in Leptothrix sheaths, it is still unknown how these chemical bonds are formed in the sheaths: are the iron hydroxides and oxides formed first, then other ions bind to them or vice versa?…”
Section: Ed/xrd-results and Crystallinity Of Sheathsmentioning
confidence: 99%
“…The uniqueness of the two sheaths may reflect the fact that they are not degraded by the commonly available proteases and glycosidases. 9,25) These structures are drawn based on assumptions that every pentasaccharide repeating unit has a peptide side chain and that the amino sugar residues free of the peptide side chain are not derivatized. The residue numbers in parentheses correspond to those indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%